2022
DOI: 10.1111/head.14284
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of acute and preventive therapies for episodic and chronic cluster headache: A scoping review of the literature

Abstract: Background: Cluster headache is the most common primary headache disorder of the trigeminal autonomic cephalalgias, and it is highly disabling.Objective: We undertake a scoping review to characterize therapies to prevent and acutely treat cluster headache, characterize trial methodology utilized in studies, and recommend future trial "good practices." We also assess homogeneity of studies and feasibility for future network meta-analyses (NMAs) to compare acute and preventive treatments for cluster headache. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 82 publications
0
3
0
1
Order By: Relevance
“…32,33,36 A scoping review of the literature concluded that the quality of treatment studies in chronic cluster headache did not allow to perform a network meta-analysis. 52 Several of the drugs listed in Table 2 may induce adverse reactions, especially at the highest doses tested in the literature. This requires careful monitoring of the patients to capture and address incident adverse events.…”
Section: Prevention Of Chronic Cluster Headachementioning
confidence: 99%
See 1 more Smart Citation
“…32,33,36 A scoping review of the literature concluded that the quality of treatment studies in chronic cluster headache did not allow to perform a network meta-analysis. 52 Several of the drugs listed in Table 2 may induce adverse reactions, especially at the highest doses tested in the literature. This requires careful monitoring of the patients to capture and address incident adverse events.…”
Section: Prevention Of Chronic Cluster Headachementioning
confidence: 99%
“…Most recommendations for treatment of chronic cluster headache are based on case reports, small placebo-controlled studies, or open-label studies (Table 2). A scoping review of the literature concluded that the quality of treatment studies in chronic cluster headache did not allow to perform a network meta-analysis . Several of the drugs listed in Table 2 may induce adverse reactions, especially at the highest doses tested in the literature.…”
Section: Management Of Chronic Cluster Headachementioning
confidence: 99%
“…Galcanezumab was shown to significantly reduce the occurrence of CH attacks during the first three weeks of treatment in a Phase 3, randomized, double blind, placebo-controlled study among patients with ECH (28). However, similar trials in CCH (galcanezumab and fremanezumab) and another trial in ECH (fremanezumab) did not reach the primary endpoints or were halted (29,30). In a report of 22 CCH patients (6 with comorbid migraine) treated with off-label galcanezumab or erenumab who had received insufficient response to other preventive treatments, 55% were 50% responders, experiencing a rapid and significant reduction in attack frequency and pain intensity (31).…”
Section: Cch: Chronic Cluster Headachementioning
confidence: 99%
“…Es gibt relativ wenig gute Daten zum NDPH. Eine retrospektive Auswertung der Daten von 328 Patienten wurde im Kopfschmerzzentrum in Houston durchgeführt [65] Das mittlere Alter der Patienten lag bei 40,3 Jahren; 65% waren Frauen. Die mediane Dauer des NDPH bei der ersten Konsultation betrug 0,7 Jahre.…”
Section: Andere Kopf-und Gesichtsschmerzenunclassified